Glasses-type wearable computer displays : usability considerations examined with a 3D glasses case study - Chang, Joonho (2020)
This study presents usability considerations and solutions for the design of glasses-type wearable computer displays and examines their effectiveness in a case study. Design countermeasures were investigated by a four-step design process: (1) preliminary design analysis; (2) design idea generation; (3) final design selection; and (4) virtual fitting trial. Three design interventions were devised from the design process: (1) weight balance to reduce pressure concentrated on the nose, (2) compliant temples to accommodate diverse head sizes and (3) a hanger mechanism to help spectacle users hang their wearable display on their eye glasses. To investigate their effectiveness, in the case study, the novel 3D glasses adopting the three interventions were compared with two existing 3D glasses in terms of neck muscle fatigue and subjective discomfort rating. While neck muscle fatigue was not significantly different among the three glasses (p = 0.467), the novel glasses had significantly smaller discomfort ratings (p = 0.009). Relevance to Industry: A four-step design process identified usability considerations and solutions for the design of glasses-type wearable computer displays. A novel 3D glasses was proposed through the process and its effectiveness was validated. The results identify design considerations and opportunities relevant to the emerging wearable display industry.